2018
DOI: 10.1007/s11469-018-9973-x
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use, Social Needs, and Social Support Among Youth

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science+Business Media, LLC, part of Springer Nature. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to selfarchive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…For adolescents with high or medium levels of PIU, low social integration was an associated factor for PIU, which further indicated that social integration can play an important role in prevention for adolescents with a relatively higher risk of PIU. This is consistent with previous findings that higher social skills and higher levels of social support are associated with lower PIU ( Bolat et al, 2018 ; Chi-Ying, 2018 ; Prievara et al, 2018 ). Namely, being passionate about helping others, as the main characteristic of social integration, will expand and strengthen individuals’ social networks, and will provide more social support and sense of belonging in the real world ( Davids et al, 2016 ), and thus make it easier to avoid internet addiction ( Mo et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…For adolescents with high or medium levels of PIU, low social integration was an associated factor for PIU, which further indicated that social integration can play an important role in prevention for adolescents with a relatively higher risk of PIU. This is consistent with previous findings that higher social skills and higher levels of social support are associated with lower PIU ( Bolat et al, 2018 ; Chi-Ying, 2018 ; Prievara et al, 2018 ). Namely, being passionate about helping others, as the main characteristic of social integration, will expand and strengthen individuals’ social networks, and will provide more social support and sense of belonging in the real world ( Davids et al, 2016 ), and thus make it easier to avoid internet addiction ( Mo et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Masten (2001) suggested that living an engaged life would be beneficial in helping youths avoid poor choices that result in delinquent behaviors and thus increase their resilience to addictive behavior. Specifically, social integration, as an ability of engaging in social networks and life, has a positive effect on social relations, which is suggested to be a key factor of PIU (Prievara et al, 2018). PIU is positively related to social relational styles such as low social skill (Chi-Ying, 2018) and shyness (Prievara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies showed that when social resources are relatively scarce, some people choose the internet or cannabis use as a medium through which to meet their needs and gain social support, especially when they are required to reestablish social networks because of environmental changes ( Carter et al, 2016 , Yao and Zhong, 2014 , Zhang et al, 2018 ). Perceived lack of social support has been found to be indirectly associated with PIU ( Prievara, Piko, & Luszczynska, 2019 ) and, additionally, PIU has been found to be less common in those who perceive more social support ( Gunuc & Dogan, 2013 ). Lack of social support has been found to increase the likelihood of CUD ( van der Pol et al, 2013b , van der Pol et al, 2013a ).…”
Section: Introductionmentioning
confidence: 99%